French imports: English translations of Molière, 1663-1732 - Jones, S (2016)
This thesis explores the first English translations of Molière's works published between 1663 and 1732 by writers that include John Dryden, Edward Ravenscroft, Aphra Behn, and Henry Fielding. It challenges the idea that the translators straightforwardly plagiarized the French plays and instead argues that their work demonstrates engagement with the dramatic impact and satirical drive of the source texts. It asks how far the process of anglicization required careful examination of the plays' initial French national context. The first part of the thesis presents three fundamental angles of interrogation addressing how the translators dealt with the form of the dramatic works according to theoretical and practical principles. It considers translators' responses to conventions of plot formation, translation methods, and prosody. The chapters are underpinned by comparative assessments of contextual theoretical writings in French and English in order to examine the plays in the light of the evolving theatrical tastes and literary practices occasioned by cross-Channel communication. The second part takes an alternative approach to assessing the earliest translations of Molière. Its four chapters are based on close analysis of culturally significant lexical terms which evoke comically contentious social themes. This enquiry charts the changes in translation-choices over the decades covered by the thesis corpus. The themes addressed, however, were relevant throughout the period in both France and England: marital discord caused by anxieties surrounding cuckoldry and gallantry, the problems of zealous religious ostentation, the dubious professional standing of medical practitioners, and bourgeois social pretension. This part assesses how the key terms in translation were chosen to resonate within the new semantic fields in English, a target language which was coming into close contact with new French terms.